Changes of Motor Control of Distal Joint and Motor Learning in Badminton Hitting Skills According to the Visual Feedback Types (Focused on Performance Curves) - Donghwi Suh (Asian Society of Kinesiology, 2023)
OBJECTIVES This study aims to compare the change of motor control of distal joint while badminton hitting on novice in accordance with visual feedback type. METHODS We offered digitized graph and 3D animation of upper limb to quantitative feedback(QN) group, and qualitative feedback(QL) group respectively. Dependent variables are kinematic variable of wrist joint. 27 young men were recruited into three groups, asked to perform forehand-underclear. 20trials for pre-test, 150trials for practice, each 20trials for post-test and retention-test were progressed. After each 10trials in practice step, we offered each feedbacks to each groups. Two-way repeated ANOVA was used to investigate the results. RESULTS Maximum extension angle and Maximum flexion angular velocity of wrist joint improved faster than QN in early phase, but in Maximum flexion angular velocity QL improved more than QN on late phase. CONCLUSIONS Finding showed that QN improves motor control of distal joint during badminton stroke on early phase but QL may improve more on late phase. In conclusion, this study presents a new direction for the mechanism of motor control and cognitive structure for the distal joint of motor skills forming proximaldistal coordination patterns.